2016
DOI: 10.1242/jcs.181768
|View full text |Cite
|
Sign up to set email alerts
|

Kinectin-dependent ER transport supports the focal complex maturation required for chemotaxis in shallow gradients

Abstract: Chemotaxis in shallow gradients of chemoattractants is accomplished by preferential maintenance of protrusions oriented towards the chemoattractant; however, the mechanism of preferential maintenance is not known. Here, we test the hypothesis that kinectindependent endoplasmic reticulum (ER) transport supports focal complex maturation to preferentially maintain correctly oriented protrusions. We knocked down kinectin expression in MDA-MB-231 cells using small interfering RNA and observed that kinectin contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Surprisingly, the migration and invasion abilities and cell viability were attenuated in KTN1-KO cells compared to Huh7-WT cells, indicating that KTN1 may enhance cell viability and promote cell migration and invasion in HCC. A previous study reported the role of KTN1 in contributing to the direction of cell migration in breast cancer cells [22], and another disturbed the interaction between KTN1 proteins and kinesin and observed that cell migration was hindered [37]. Such studies point to the promotion effect of KTN1 on cells.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Surprisingly, the migration and invasion abilities and cell viability were attenuated in KTN1-KO cells compared to Huh7-WT cells, indicating that KTN1 may enhance cell viability and promote cell migration and invasion in HCC. A previous study reported the role of KTN1 in contributing to the direction of cell migration in breast cancer cells [22], and another disturbed the interaction between KTN1 proteins and kinesin and observed that cell migration was hindered [37]. Such studies point to the promotion effect of KTN1 on cells.…”
Section: Discussionmentioning
confidence: 87%
“…Kinectin 1, encoded by KTN1 (also called KNT, CG1, and MU-RMS- 40.19), belongs to an integral membrane protein in the endoplasmic reticulum and participates in organelle transportation [22]. The KTN1 gene is renowned for its relationships with axon transport and cell mitosis [23], and the KTN1 protein regulates the expression of other proteins by binding to translational elongation factor (EF)-δ and participating in the assembly of the EF-1 complex [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Kinectin was identified using a function-blocking monoclonal antibody [196] and binds to the KIF5 C-terminus [197]. Kinectin has been implicated in the regulation of focal adhesion dynamics during chemotaxis by promoting ER targeting to focal adhesions at the cell's leading edge [198,199]. Interestingly, Rab18 is required for this process and forms a ternary complex with kinectin and kinesin-1 [198].…”
Section: Microtubule Motors Drive Er Dynamicsmentioning
confidence: 99%
“…However, as the molecular mechanisms used by Rab18 in cell migration are not fully elucidated, we aimed to characterize its role in this process. Interestingly, KNT1, an integral ER membrane protein that binds to the motor protein kinesin to mediate microtubule plus-end-directed transport, promotes the anterograde ER transport to support FA maturation during chemotaxis (Ng et al, 2016;Ong et al, 2000;Zhang et al, 2010). We therefore wondered whether the role of Rab18 in cell migration could be connected to KNT1 function.…”
Section: Rab18 Directly Interacts With Knt1mentioning
confidence: 99%
“…KNT1 is an integral transmembrane protein that connects the ER to the microtubule motor kinesin-1 (Ong et al, 2000). Evidence indicates that KNT1-kinesin interaction mediates the anterograde transport of the ER to support FA growth and maturation during cell migration, but what regulates the KNT1kinesin-mediated transport of the ER to the leading edge remains unresolved (Ng et al, 2016;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%